Partnering for Quail in South Carolina: A Cooperative Approach Making a Difference - Gary M. Peters; Michael Wayne Hook; Mark S. Garner; Jeffrey M. Magniez; Charles W. McKinney; Jordan S. Nanney (National Quail Symposium Proceedings, 2017)
The National Bobwhite Conservation Initiative (NBCI) identified 15 national quail focal areas throughout the distribution of the northern bobwhite (Colinus virginianus) in June 2016. The first NBCI Focal Area on U.S. Forest Service System land emerged from the existing 16,200-hectare Indian Creek Woodland and Savanna Restoration Initiative (ICWSRI). The ICWSRI is an ongoing collaborative project involving partners from 10 agencies and organizations in the Piedmont of South Carolina. Cooperation among federal and state agencies, non-governmental organizations (NGO), and private landowners, combined with assistance programs such as the Environmental Quality Incentives Program (EQIP) have currently resulted in 2,547 hectares (1,600 hectares on private land and 947 hectares on public land) of improved habitat for wildlife species associated with pine woodlands and savannas. Data obtained through the Breeding Bird Survey, spring whistle counts, and fall covey counts suggest a correlation between woodland and savanna restoration and avian response across the ICWSRI area. Fall covey count minimum population estimates (birds/ha) ranged from 1/38 in 2008 to 1/7 in 2016. Spring whistle count population density estimates (birds/ha) ranged from 1/37 in 2009 to 1/6 in 2012. Although monitoring suggests an initial increase in bobwhite densities across the project area, it is imperative to continue involving existing and additional partners to increase habitat availability, connectivity, and quality for bobwhite and associated species. Collaborative efforts and partnerships across ownership boundaries are necessary to increase bobwhite populations on a landscape scale. The Indian Creek project has effectively involved efforts from federal, state, NGO, and private partners to restore and improve bobwhite habitat and may serve as an example for other areas where incorporating a cooperative approach could positively influence bobwhite populations.
Keywords: colinus virginianus; northern bobwhite; habitat restoration; Indian Creek; partnerships; savanna; woodland